Research Progress on the Relationship between Ischemic Stroke and Immunoinflammatory Factors - Qiang TANG; Huilin HUANG; Luwen ZHU; Hongyu LI; Jiyao ZHANG; Ping QIN; Xia YIN; Jiashuai LI (康复学报)
With the development of aging society, the number of stroke patients in China has been rising steadily, and ischemic stroke accounts for a large proportion. At present, the problem of ischemic stroke has aroused wide public concern. China is facing an increasingly severe situation of prevention and treatment, and the disease has brought a heavy burden to patients, families and even the whole society, which has become one of the focuses and difficulties of modern medical research. Many studies have shown that inflammatory response plays an important role in the occurrence and development of ischemic stroke and participates in the process of pathological injury. At the same time, inflammatory response in the late stage to participate in the recovery of the disease, to protect and repair the nerve, play a dual role. Inflammatory response may be one of the targets in the treatment of ischemic stroke and has a significant research value. Inflammatory response is an important part of physiological and pathological changes of ischemic stroke, which determines the transformation and prognosis of stroke. Immunotherapy for inflammatory response is one of the hot spots at present, with a broad prospect. FasL, microglia and T lymphocytes are involved in the process of ischemic stroke and are closely related to inflammatory response. FasL can induce cell apoptosis and immune inflammatory response, and microglia and T lymphocytes all play protective or damaging roles to varying degrees, which can greatly broaden the treatment thinking and plan of ischemic stroke and meet the diversified challenges in the treatment of stroke. Therefore, FasL, microglia and T lymphocytes can be used to further explore the relationship between inflammatory response and ischemic stroke, providing a solid theoretical basis for clinical promotion and application. This article reviews the research progress of immune inflammatory response stage in ischemic stroke and its relationship with FasL, microglia and T lymphocytes.